2021
DOI: 10.3390/ijerph18105155
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Evaluation of Different Types of Recovery in National Level Paralympic Powerlifting

Abstract: Background: Recovery from training is vital as it ensures training and performance to continue at high intensities and longer durations to stimulate the body and cause further adaptations. Objective: To evaluate different methods of post-workout recovery in Paralympic powerlifting athletes. Methods: Twelve male athletes participated (25.4 ± 3.3 years; 70.3 ± 12.1 kg). The presence of muscle edema, pain threshold, plasma cytokines, and performance measurement were evaluated five times. The recovery methods used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 35 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…However, the assessment of the internal training load must be based on psychological and physiological indicators, as physiological mechanisms can mediate psychological responses in a training process [8,54]. In this study, we focused on evaluating the stress generated by training through psychological indicators owing to the practicality of the instruments; however, more sensitive physiological indicators have been used to control internal training load in PP, according to Fraga et al [17], creatine kinase and lactate dehydrogenase to control muscle damage in a training session, as well as dry needling and immersion in ice water as recovery techniques in PP [55]. Adverse psychological effects have been observed, as revealed in the state of mood, during a period of training in athletes of strength sport [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, the assessment of the internal training load must be based on psychological and physiological indicators, as physiological mechanisms can mediate psychological responses in a training process [8,54]. In this study, we focused on evaluating the stress generated by training through psychological indicators owing to the practicality of the instruments; however, more sensitive physiological indicators have been used to control internal training load in PP, according to Fraga et al [17], creatine kinase and lactate dehydrogenase to control muscle damage in a training session, as well as dry needling and immersion in ice water as recovery techniques in PP [55]. Adverse psychological effects have been observed, as revealed in the state of mood, during a period of training in athletes of strength sport [10].…”
Section: Discussionmentioning
confidence: 99%
“…Week 1 served for familiarization and the performance of the 1RM test, where each subject started the attempts with a weight they believed they could lift only once using maximum effort, and weight increments were added until reaching the maximum load that could be lifted all at once. If the practitioner could not perform a single repetition, 2.4% to 2.5% of the load used in the test was subtracted [ 16 , 28 ]. Subjects rested for 3–5 min between trials.…”
Section: Methodsmentioning
confidence: 99%
“…Powerlifting is characterized as a strength sport where the squat, bench press, and deadlift are performed [ 14 , 15 ], and through the adapted bench press in Paralympic powerlifting (PP) [ 16 ]. Studies have shown that powerlifting can be an alternative to prevent and/or control HBP [ 2 , 11 ]; however, to date, there has been no comparison between people with and without disabilities in the powerlifting bench press.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the hemodynamic response may be affected when high-load resistance exercise is performed. Hemodynamics is a set of physiological responses related to the pumping of blood by the cardiovascular system, and includes blood pressure, heart rate, blood flow, among others [4,5].…”
Section: Introductionmentioning
confidence: 99%